Pterostilbene Promotes Mean Lifespan in Both Male and Female Drosophila Melanogaster Modulating Different Proteins in the Two Sexes. (16th February 2022) - Beghelli, Daniela; Zallocco, Lorenzo; Barbalace, Maria Cristina; Paglia, Simona; Strocchi, Silvia; Cirilli, Ilenia; Marzano, Valeria; Putignani, Lorenza; Lupidi, Giulio; Hrelia, Silvana; Giusti, Laura; Angeloni, Cristina
Abstract : Aging is a multifactorial phenomenon characterized by degenerative processes closely connected to oxidative damage and chronic inflammation. Recently, many studies have shown that natural bioactive compounds are useful in delaying the aging process. In this work, we studied the effects of an in vivo supplementation of the stilbenoid pterostilbene on lifespan extension in Drosophila melanogaster . We found that the average lifespan of flies of both sexes was increased by pterostilbene supplementation with a higher effect in females. The expression of longevity related genes (Sir2, Foxo, and Notch) was increased in both sexes but with different patterns. Pterostilbene counteracted oxidative stress induced by ethanol and paraquat and up-regulated the antioxidant enzymes Ho e Trxr-1 in male but not in female flies. On the other hand, pterostilbene decreased the inflammatory mediators dome and egr only in female flies. Proteomic analysis revealed that pterostilbene modulates 113 proteins in male flies and only 9 in females. Only one of these proteins was modulated by pterostilbene in both sexes: vacuolar H[+] ATPase 68 kDa subunit 2 (Vha68-2) that was strongly down-regulated. These findings suggest a potential role of pterostilbene in increasing lifespan both in male and female flies by mechanisms that seem to be different in the two sexes, highlighting the need to conduct nutraceutical supplementation studies on males and females separately in order to give more reliable results.